2002
DOI: 10.1152/ajpregu.00643.2001
|View full text |Cite
|
Sign up to set email alerts
|

Contractile properties and myosin expression in rats born and reared in hypergravity

Abstract: The effects of hypergravity (HG) on soleus and plantaris muscles were studied in Long Evans rats aged 100 days, born and reared in 2-g conditions (HG group). The morphological and contractile properties and the myosin heavy chain (MHC) content were examined in whole muscles and compared with terrestrial control (Cont) age-paired rats. The growth of HG rats was slowed compared with Cont rats. A decrease in absolute muscle weight was observed. An increase in fiber cross-sectional area/muscle wet weight was demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…In a recent study on rats reared in HG (Picquet et al, 2002), we showed that the slow soleus muscle studied in situ presented an increase in maximal and twitch tensions and was changed into a slower type, for both contractile parameters and MHC isoform content, while the fast plantaris was less affected. Therefore the results obtained under lifelong conditions of hypergravity, when compared to both microgravity and hypergravity applied to adults, appeared opposite in terms of generated forces and MHC isoform transitions.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…In a recent study on rats reared in HG (Picquet et al, 2002), we showed that the slow soleus muscle studied in situ presented an increase in maximal and twitch tensions and was changed into a slower type, for both contractile parameters and MHC isoform content, while the fast plantaris was less affected. Therefore the results obtained under lifelong conditions of hypergravity, when compared to both microgravity and hypergravity applied to adults, appeared opposite in terms of generated forces and MHC isoform transitions.…”
Section: Introductionmentioning
confidence: 81%
“…For this purpose, the different objectives of this work were: (1) analysis, at the cellular level, of the Ca 2+ activation characteristics in relation to the forces developed by single fibers, in order to complete the study of Picquet et al (2002), who showed, at the whole muscle level, a reduction of the absolute twitch and maximal tetanic forces, as well as a decrease in fiber cross sectional area after HG. (2) To study more deeply phenotype acquisition in muscles continuously exposed to 2·g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Section 1734 solely to indicate this fact. portant role in determining how fast the fiber can be activated and relax (41).In the adult Long-Evans hooded rat, EDL and SOL muscles do not overlap in their patterns of MHC expression and fiber type composition, with the EDL muscle containing only type IIB and IID fibers and a small fraction of type IIB/D hybrid fibers (14) and SOL containing only type I and IIA fibers and a small fraction of type I/IIA hybrid fibers (14,35). In this study we used mechanically skinned muscle fiber preparations from Long-Evans hooded rats to investigate MHC isoform expression, SR properties, and contractile activation characteristics at the single fiber level.…”
mentioning
confidence: 99%